Maximum carbonyl‐coordination number of scandium Computational study of Sc(CO)n (n = 1–7), Sc(CO)7− and Sc(CO)63−. Issue 8 (12th July 2012) - Gao, Si‐Meng; Guo, Wen‐Ping; Jin, Lin; Ding, Yi‐Hong
Abstract Understanding the maximum bonding ability is very important with the potential both to design new compounds and to broaden chemists' imagination. While the coordination ability of the late transition metals has been richly understood, that of scandium is very poor. In this work, a detailed computational study on the equilibrium geometries, stability and vibrational frequencies of a series of Sc(CO)n (n = 1–7), Sc(CO) 7−<inline-graphic xlink:href="ark:/27927/pgg1w52pwqv" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> and Sc(CO) 63−<inline-graphic xlink:href="ark:/27927/pgg1w52pwp9" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> is reported using density functional theory functionals and the coupled cluster (single‐point) method with 6‐311+G(3df) basis set. It was shown that the obtained sequential and average CO binding energies of Sc(CO)n (n = 4–7), Sc(CO) 7−<inline-graphic xlink:href="ark:/27927/pgg1w52pwnr" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> and Sc(CO) 63−<inline-graphic xlink:href="ark:/27927/pgg1w52pwm6" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> are comparable to those of the experimentally known species, i.e., smaller Sc‐carbonyls (n ≤3) and the analog Ti(CO)7+. Thus, the studied high scandium carbonyls could all be experimentally accessible. In addition, the studied Sc(CO)n generally favor the low‐spin ground state (doublet) structures except ScCO and Sc(CO)3 that are in the quartet states. The previously uncertain spectrum bands were assigned to Sc(CO)4 and Sc(CO)5 in this work. In all, the appreciable stability suggested that the last 18‐electron first‐row transition metal carbonyls, that is, Sc(CO) 7−<inline-graphic xlink:href="ark:/27927/pgg1w52pwkn" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> and Sc(CO) 63−<inline-graphic xlink:href="ark:/27927/pgg1w52pwj3" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />, could be accessible in experiment. © 2013 Wiley Periodicals, Inc.